Participation in Younger and Older Adults Post-stroke: Frequency, Importance, and Desirability of Engagement in Activities - Toglia, Joan; Askin, Gulce; Gerber, Linda M.; Jaywant, Abhishek; O'Dell, Michael W. (Frontiers in Neurology, 2019)
Purpose: To characterize and compare frequency and subjective dimensions of post-stroke participation in younger (< 65) and older adults (> age 65), in social, productivity and leisure activities, 6 months post inpatient rehabilitation. Secondary aims included exploration of demographic and clinical factors influencing desire for increased participation and comparison of two measures of participation. Methods: A prospective cohort study of people with stroke (n=99) who were identified during their inpatient rehabilitation stay and followed-up 6 months post discharge with telephone interviews using two self-report participation measures. The Stroke Impact Participation subscale (SIS-P) measured the frequency of perceived limitations in social, leisure, productive activities and extent of stroke recovery. The Community Participation Indicators (CPI) examined activity frequency, importance, and desire for increased activity engagement. Descriptive statistics were used to summarize demographic variables and characterize SIS-P and CPI items. Differences between age groups on individual items were examined. Associations between measures and demographic variables were explored. Results: Both groups reported a wide variation in participation restrictions that was not associated with stroke severity and weakly associated with discharge functional status (rho = .20-.35). There were no significant differences between age groups in CPI frequency (for 18/19 items), or the SIS-P. However, there was a trend toward more participation restrictions on the SIS-P among those < 65 (p = .07). Younger adults (n = 46; median age = 53) were significantly more likely to indicate that they were not doing selected activities enough on the CPI, compared with older adults (n = 56; median age = 76). While age and ethnicity were independently associated with some activities, it was not associated with other activities. The CPI and SIS-P were moderately related at a correlation of rho= .54, p <.001. Conclusion: The CPI demonstrated value and utility in examining subjective perspectives of activity importance and desire for change for people who are 6 months post-stroke. Although the CPI and SIS-P are moderately related, subjective appraisal of participation in selected individual activities (CPI) better distinguished between age groups and provided unique and distinct information from the SIS-P.